DOI: 10.11606/d.3.2012.tde-26072013-114250
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação laboratorial e de campo da tecnologia de reciclagem de base com cimento para a reabilitação de pavimentos.

Abstract: Aos meus pais Walkiria e Domingos, pelo amor, ensinamentos e incentivos. Aos meus irmãos André e Gabriela, pelos bons e maus exemplos. Aos meus sobrinhos Neto, Carol, Camila, Andrézinho e Pedro, por todos os momentos felizes. À minha orientadora Professora Kamilla Vasconcelos, pelo o aprendizado, carinho, dedicação e paciência. À Professora. Liedi Bernucci por toda a disposição em ensinar, orientar e aconselhar. À minha grande amiga Amanda Marcandali, por tantas contribuições positivas a esse trabalho. Aos alu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…The compaction effort causes similar effects as the cement content; that is, when increased, it reduces the mixture porosity and increases its strength and stiffness [30,73,104]. Aranha [26] states that this effect is stronger on compressive behaviour than on tensile behaviour. Besides, Fedrigo et al [53] observed the same trend for conventional cement stabilised materials.…”
Section: Compaction Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…The compaction effort causes similar effects as the cement content; that is, when increased, it reduces the mixture porosity and increases its strength and stiffness [30,73,104]. Aranha [26] states that this effect is stronger on compressive behaviour than on tensile behaviour. Besides, Fedrigo et al [53] observed the same trend for conventional cement stabilised materials.…”
Section: Compaction Effectmentioning
confidence: 99%
“…Furthermore, FDR-PC pavements generally show lower deflections than pavements recycled with other cold technologies [51,52]. After recycling, deflections continue to reduce since the FDR-PC layer stiffness continues to increase due to curing [20,21,26,52,81,99,114].…”
Section: Field Behaviourmentioning
confidence: 99%
“…The concurrent increase of soil percentage in 10% and the decrease of aggregate percentage reduced the UCS values of SAC 30:70 mixtures (~19%). The same behavior was also reported in other studies that compared SAC with varying material proportions (ARANHA, 2013;FEDRIGO et al, 2017;GHANIZADEH et al, 2017). Overall, the increase of cement content improves UCS values and this is remarkable at 7 and 28 days of curing.…”
Section: Unconfined Compressive Strength Testsupporting
confidence: 85%
“…Não fez parte do escopo desta pesquisa avaliar as propriedades mecânicas do material reciclado ao variar percentuais de cimento, asfalto fresado, energia de compactação e tempo de cura dos corpos de prova, pois seus efeitos já são bastante conhecidos e existem muitos trabalhos publicados na literatura nacional e estrangeira em que os autores fizeram uso dessas variáveis, como: Kolias (1996) e Kolias, Katsakou e Kaloidas (2001); Abdo (2001); Dellabianca (2004); Cooley (2005); Brown (2006); Crane et al (2006); Moreira (2006); Guthrie, Brown e Eggett (2007); Minguela (2011); Aranha (2013); Tolbert (2014); Yang e Wu (2014); Fedrigo (2015); Kleinert (2016) e Castañeda (2016).…”
Section: Delimitações Do Estudounclassified
“…É necessário enfatizar a adoção de um procedimento semelhante àqueles empregados nas pesquisas de Luvizão (2014), Aranha (2013) e Fedrigo (2015).…”
Section: Escolha Do Tipo De Cimentounclassified